Genetic and self‐perceived ancestries in Argentina: Beyond the three‐hybrid model. Issue 1 (6th February 2023) - Ruderman, Anahí; Luisi, Pierre; Paschetta, Carolina; Teodoroff, Tamara; Pérez, Luis Orlando; de Azevedo, Soledad; Trujillo‐Jiménez, Magda Alexandra; Navarro, Pablo; Morales, Leonardo; Pazos, Bruno; González‐José, Rolando; Ramallo, Virginia
Abstract: Objectives: The increased availability of genome‐wide data allows capturing the fine genetic structure of present days populations. Here we analyze the genetic ancestry at a fine scale of an Argentinean Patagonia population to understand the origins beyond the three‐hybrid model, and to compare these results with volunteers' self‐perceived ancestry in a broad context encompassed by historical and familiar information. Materials and Methods: We compare high‐throughput genotyping data for 92 individuals that we generated to data sets from the literature by applying fully haplotype‐based methods to examine patterns of human population substructure. The volunteers filled out a semi‐structured questionnaire, including questions about their history, ancestors, and self‐perceived ancestry. Finally, we used non‐parametric tests in order to compare genomic ancestry against self‐perception. Results: Genetic ancestry from Iberian populations accounted for 0.176 (Spain and Basque origins), while the component associated with Italian populations accounted for 0.140. We observed a 0.169 Native American genetic ancestry. Participants significantly over‐ and under‐ self‐perceived Native American and European origins, respectively. Components of origins from North Africa to Central South Asia accounted for 0.225 of the genetic ancestry in the sample, with significantly higher proportions for people that mentioned such origins in their genealogical history. Discussion: We captured the fine‐genetic architecture of a Puerto Madryn population sample in Chubut province, showing that self‐perceived ancestry remains a poor proxy for genetic ancestry. The presence of North Africa to Central South Asia components and its correlate with self‐perception of these origins justifies its inclusion in future miscegenation studies in Argentina.